Bioactive strontium ions/ginsenoside Rg1–incorporated biodegradable silk ﬁbroin-gelatin scaffold promoted challenging osteoporotic bone regeneration - Wu, Tingting; Liu, Wenping; Huang, Shusen; Chen, Jiwen; He, Fupo; Wang, Huajun; Zheng, Xiaofei; Li, Zhenyan; Zhang, Huantian; Zha, Zhengang; Lin, Zefeng; Chen, Yuanfeng (Materials today bio, 2021)
Autogenous healing of osteoporotic fractures is challenging, as the regenerative capacity of bone tissues is impaired by estrogen reduction and existed pro-inflammatory cytokines. In this study, a biofunctional ginsenoside Rg1 and strontium-containing mineral (SrHPO4, SrP)-incorporated biodegradable silk ﬁbroin-gelatin (SG) scaffold (Rg1/SrP/SG) was developed to stimulate the osteoporotic bone repair. The incorporation of 15 wt% SrP significantly enhanced the mechanical strength, stimulated the osteogenic differentiation of mouse bone marrow mesenchymal stem cells, and suppressed the osteoclastogenesis of RAW264.7 in a concentration-related manner. The loading of Rg1 in SG and 15SrP/SG scaffolds obviously promoted the angiogenesis of human umbilical vein endothelial cells via activating the expression of vascular endothelial growth factor and basic fibroblast growth factor genes and proteins. The bioactive strontium ions (Sr2+) and Rg1 released from the scaffolds together mediated lipopolysaccharide-treated macrophages polarizing into M2 type. They downregulated the expression of inflammatory-related genes (interleukin (IL)-1β, tumor necrosis factor α, and IL-6) and stimulated the expression of genes related to anti-inflammation (Arginase and IL-10) as well as bone repair (BMP-2 and PDGF-BB) in the macrophages. The in vivo results also displayed that SrP and Rg1 significantly promoted the bone repair effect of SG scaffolds in osteoporotic critical-sized calvarial defects. Besides, the degradation rate of the scaffolds was close to the bone regeneration rate. Therefore, the simultaneous addition of SrP and Rg1 is a promising way for facilitating the osteoporotic bone repair activity of SG scaffolds via promoting the osteogenesis and angiogenesis, as well as inhibiting the osteoclastogenesis and inflammation. [Display omitted]